Polymer-like tetramer acceptor enables stable and 19.75% efficiency binary organic solar cells - Jianxiao Wang; Cheng Sun; Yonghai Li; Fuzhen Bi; Huanxiang Jiang; Chunming Yang; Xichang Bao; Junhao Chu (Nature Communications)
Abstract Limited by large batch differences and inferior polymerization degree of current polymer acceptors, the potential high efficiency and stability advantages of all-polymer solar cells (all-PSCs) cannot be fully utilized. Alternatively, largely π-extended and structurally definite oligomer acceptors are effective strategies to realize the overall performance of polymer acceptors. Herein, we report a linear tetramer acceptor namely 4Y-BO with identical molecular skeleton and comparable molecular-weight relative to the control polymer acceptor PY-BO. The structurally definite tetramer shows refined film-forming kinetics and improved molecular ordering, offering uniform crystallinity with polymer donor and hence well-defined fibrous heterojunction textures. Encouragingly, the PM6:4Y-BO devices achieve an efficiency up to 19.75% (certified efficiency:19.58%), largely surpassing that of the control PM6:PY-BO device (15.66%) and ranks the highest among solar cells based on oligomer and polymer acceptors. More noticeably, thermal stability, photostability and mechanical flexibility are collectively enhanced for PM6:4Y-BO devices. Our study provides an important approach for fabricating high performance and stable organic photovoltaics.